Comparison of epicardial adipose tissue radiodensity threshold between contrast and non-contrast enhanced computed tomography scans: A cohort study of derivation and validation. (August 2018) - Xu, Lingyu; Xu, Yuancheng; Coulden, Richard; Sonnex, Emer; Hrybouski, Stanislau; Paterson, Ian; Butler, Craig
Abstract: Background and aims: Epicardial adipose tissue (EAT) volume derived from contrast enhanced (CE) computed tomography (CT) scans is not well validated. We aim to establish a reliable threshold to accurately quantify EAT volume from CE datasets. Methods: We analyzed EAT volume on paired non-contrast (NC) and CE datasets from 25 patients to derive appropriate Hounsfield (HU) cutpoints to equalize two EAT volume estimates. The gold standard threshold (−190HU,  −30HU) was used to assess EAT volume on NC datasets. For CE datasets, EAT volumes were estimated using three previously reported thresholds: (−190HU,  −30HU), (−190HU,  −15HU), (−175HU,  −15HU) and were analyzed by a semi-automated 3D Fat analysis software. Subsequently, we applied a threshold correction to (−190HU,  −30HU) based on mean differences in radiodensity between NC and CE images (ΔEATrd = CE radiodensity - NC radiodensity). We then validated our findings on EAT threshold in 21 additional patients with paired CT datasets. Results: EAT volume from CE datasets using previously published thresholds consistently underestimated EAT volume from NC dataset standard by a magnitude of 8.2%–19.1%. Using our corrected threshold (−190HU, −3HU) in CE datasets yielded statistically identical EAT volume to NC EAT volume in the validation cohort (186.1 ± 80.3 vs. 185.5 ± 80.1 cm 3, Δ = 0.6 cm 3, 0.3%, p  = 0.374). Conclusions: Estimating EAT volume from contrast enhanced CT scans using a corrected threshold of −190HU, −3HU provided excellent agreement with EAT volume from non-contrast CT scans using a standard threshold of −190HU,  −30HU. Highlights: Non-contrast EAT thresholds underestimate contrast-enhanced EAT volume. Previous attempts at adjusting contrast EAT threshold did not eliminate the problem. Radiodensity difference between contrast and non-contrast EAT was 27.0U. Radiodensity difference can be used to adjust the EAT threshold for contrast CT. Thresholding contrast CT data with (−190, -3U) eliminates EAT underestimation.